Controlled Mutual Diffusion between Fullerene and Conjugated Polymer Nanopillars in Ordered Heterojunction Solar Cells. Issue 16 (6th June 2016) - Ko, Jongkuk; Song, Jiyun; Yoon, Hyunsik; Kim, Taeyong; Lee, Changhee; Berger, Rüdiger; Char, Kookheon
Abstract : A new approach is presented to control the nanomorphology of organic solar cells in a predictable, controllable, and easily‐scalable way. The nanoimprint lithography (NIL) is combined with a subsequent molecular diffusion step controlled by thermal annealing. The new approach is realized by using nanointerdigitated donor–acceptor structure, consisting of poly(3‐hexylthiophene‐2, 5‐diyl) nanopillar arrays surrounded by phenyl‐C61‐butyric acid methyl ester. Subsequent thermal annealing leads to vertically aligned ordered quasi‐bulk heterojunctions with hierarchical nanostructure. The changes are studied in nanostructural and electrical properties of the pillar samples using scanning probe microscopy. In addition, grazing‐incidence small and wide angle X‐ray scattering yield detailed quantitative information on the molecular‐ to domain‐scale nanostructures. The changes in crystal size, chain orientation, and domain composition as a function of thermal anneal temperature and time are obtained. In addition, the conductive scanning force microscopy in quantitative imaging mode, applied to the pillar‐based samples for the first time, allows us to establish a clear relationship between nanomorphology, nanoelectrical property, and macroscale device performance. It is believed that the NIL combined with controlled molecular diffusion is a powerful method, which could be easily extended to other materials and processes to realize a whole variety of other hierarchical nanomorphologies. Abstract : With controlled mutual diffusion of donor and acceptor molecules on well‐defined nanointerdigitated donor–acceptor pillar structure, quasi‐bulk heterojunction pillars are formed in large area. The pillar nanostructures are effectively controlled by varying the thermal annealing conditions, showing nano‐ to macroscale structural and electrical properties easily monitored by grazing‐incidence X‐ray scattering, and scanning force microscopy.